1989
DOI: 10.1115/1.3259003
|View full text |Cite
|
Sign up to set email alerts
|

Electro-Rheological-Fluid-Based Articulating Robotic Systems

Abstract: The limitations of the current generation of robotic systems has triggered a new research thrust for predicting the elastodynamic response of assemblages of articulating flexible-bodied systems. This research thrust is extended herein by proposing the fabrication of robotic systems in either monolithic or ultra-advanced composite laminated high-strength, high-stiffness materials in which are incorporated electro-rheological fluids. These multiphase fluid systems, which change their rheological behavior instant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As far as is known, the first application of ERFs to robotic systems was reported by Gandhi et al [1]. In this work, the forearm of a commercial parallel robot was retrofitted by inserting ERF.…”
Section: Erf-based Robotsmentioning
confidence: 96%
See 1 more Smart Citation
“…As far as is known, the first application of ERFs to robotic systems was reported by Gandhi et al [1]. In this work, the forearm of a commercial parallel robot was retrofitted by inserting ERF.…”
Section: Erf-based Robotsmentioning
confidence: 96%
“…The deflection of the forearm was successfully reduced during dynamic maneuvering and transient motions, owing to the increment of the field-dependent damping property of the ERF domain. Choi et al [2,3] performed a study similar to Gandhi et al [1], with primary focusing on the vibration control of a flexible robot arm incorporating ERF. In this work, a single-link flexible robot arm system was made by inserting ERF into the box-type aluminum arm.…”
Section: Erf-based Robotsmentioning
confidence: 99%
“…These structures are called smart sandwich structures like a smart structure in which both the natural frequency and damping property can be controlled by applying external fields such as voltage and current. The development of electrorheological (ER) fluid based sandwich structures was initiated by Gandhi et al [1][2][3]. In this work, it has been shown that the dynamic characteristics of ER fluid based sandwich structures can be tuned showing the increment of damping ratio and natural frequencies as the electric field increases.…”
Section: Introductionmentioning
confidence: 96%
“…In recent year, the magneto-rheology (MR) material was applied to the vibration control of flexible robot to improve the accuracy of movement of the end-effect by Gandhi [8]. Compared with the traditional vibration absorbing material, not only the passive control but also the semi-active control can be implemented according to the mechanical properties of MR material changing continuously with the external magnetic condition [9].…”
Section: Introductionmentioning
confidence: 99%